Refining Privacy in Tort Law - O'Callaghan, Patrick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is about privacy interests in English tort law. Despite the recent recognition of a misuse of private information tort, English law remains underdeveloped. The presence of gaps in the law can be explained, to some extent, by a failure on the part of courts and legal academics to reflect on the meaning of privacy. Through comparative, critical and historical analysis, this book seeks to refine our understanding of privacy by considering our shared experience of it. To this end, the book draws on the work of Norbert Elias and Karl Popper, among others, and compares the English law of privacy with the highly elaborate German law. In doing so, the book reaches the conclusion that an unfortunate consequence of the way English privacy law has developed is that it gives the impression that justice is only for the rich and famous. If English courts are to ensure equalitarian justice, the book argues that they must reflect on the value of privacy and explore the bounds of legal possibility.
Refining Privacy -- Three Conjectures About Privacy -- A Privacy Curve -- Comparing Hard Cases -- Conclusions.
Keywords: Law; Civil law; Mass media -- Law and legislation; Law; Private International Law, International & Foreign Law, Comparative Law; Civil Law; Theories of Law, Philosophy of Law, Legal History; Media Law; European Law